The effect of exercise therapy on pain, fatigue, bone function and inflammatory biomarkers individuals with rheumatoid arthritis and knee osteoarthritis: a meta-research review of randomized controlled trials - Fu, Xiaoting; Zhang, Liang; Wang, Cuijuan; Yue, Jun; Zhu, Hang (Frontiers in Physiology, 2025)
BackgroundAccumulating evidence suggested the potential role of exercise in alleviating rheumatoid arthritis (RA). However, whether exercise improves physical function (walk test, grip strength, muscle strength, joint assessments) and inflammatory biomarkers in patients with RA is unclear. This umbrella meta-analysis aimed to examine the effect of exercise in patients with RA.MethodPubMed, Scopus, Web of Science, Embase, and Cochrane Central Library databases were systematically searched for meta-analyses of randomized control trials (RCTs) to retrieve relevant studies. The effect sizes were pooled using a random-effects model, with standardized or weighted mean differences (SMDs or WMDs) and 95% confidence intervals (CIs) as summary statistics.ResultsSeventeen studies were included. The improving effects of exercise on fatigue levels (SMD = −0.28, 95% CI: −0.44, −0.13), pain intensity (ES = −0.50, 95% CI: −0.87, −0.14), disease activity score in joints (DAS) (WMD = −0.54, 95% CI: −0.99, −0.09; and SMD = −0.47, 95% CI: −0.64, −0.30), and ESR (ES = −0.85, 95% CI: −1.66, −0.03) were significant. No significant impact on the hand grip, muscle strength, walk test, joints and inflammatory biomarkers was observed.ConclusionExercise significantly reduces fatigue, pain, DAS, and ESR in RA but shows no impact on grip strength, muscle strength, walk test, joints, or other inflammatory biomarkers. This highlights its role in symptom management rather than broad physiological changes.